(untitled) (World Economics and Finance Bulletin, 2022)
This study aims to identify the impact of organizational culture in enhancing the knowledge-sharing behaviors of the teaching staff in the University of Tikrit , and the impact of the dimensions of organizational culture (trust, intellectual conflict, creativity and inclinations towards risk) on knowledge-sharing behaviors. The study sample reached (72). A faculty member in the University of Tikrit, where the descriptive analytical method was relied on, based on a questionnaire with good psychometric characteristics. An average level of knowledge sharing among the teaching staff in the University of Tikrit. The results also showed a statistically significant effect of all dimensions of organizational culture on knowledge sharing, where the dimensions of organizational culture explained the value of (64%) of the changes in the behavior of knowledge sharing, The results also showed that the level of organizational culture as well as the level of knowledge-sharing behavior does not differ according to different demographic variables: gender, college, academic rank, years of experience, age. Omar, the country where the last degree was obtained. A number of recommendations have been presented that work to consolidate the concept of organizational culture in the college and enhance the process of knowledge sharing among members of the teaching staff at Tikrit University